Understanding non-private label consumers' switching intention in emerging market. Issue 6 (2nd September 2019) - Aw, Eugene Cheng-Xi; Chong, Han Xi
Abstract : Purpose: The purpose of this paper is to propose and empirically test a research model encompassing marketing mix activities as antecedents of non-private label consumers' switching intention, particularly from an emerging market perspective. The study also aims to test the moderating role of general neophobia and gender. Design/methodology/approach: Focusing on non-private label consumers, the study analyzed a total of 211 questionnaire responses. Partial least squares structural equation modeling was used to test the research model. Findings: The results suggested that marketing mix activities, particularly advertising, in-store communication, and monetary promotion positively influenced private label brand attitude. Attitude positively influenced switching intention. The proposed moderating effects of general neophobia and gender in the relationship between private label brand attitude and switching intention were supported. Originality/value: This study provides empirical evidence to the effects of marketing practices on private label brand attitude from an emerging market perspective, complementing previous research which largely focused on developed market. The findings offer managerial ideas in targeting non-private label consumers. The test of moderating variables expands the understanding on attitude-intention link.